Estimation of strong motion distribution in the 1995 Kobe earthquake based on building damage data. - Yamaguchi, Naoya
The 1995 Kobe earthquake caused unprecedented damage to buildings and civil infrastructures in the city of Kobe and its surrounding areas. In order to evaluate the structura damage in this area due to the earthquake, it is important to estimate the distribution of earthquake ground motion. However, since the number of strong ground motion records is not enough in the heavily damaged areas, it is necessary to estimate the distribution using other data sources. In this paper, the fragility curves for low rise residential buildings were constructed using the recorded motions and the building damage data from the intensive field survey by the AIJ and CPIJ group. The fragility curves obtained were then employed to estimate the strong motion distribution in the district level for Kobe and the surrounding areas during the earthquake. The results may be useful to investigate the various damages caused by the earthquake.
Keywords: 1995 Kobe earthquake; Building damage; Strong motion distribution; Fragility curve; Geographic information systems